THE RELATIONSHIP BETWEEN ISLAMIC BANK AND CORPORATE SOCIAL RESPONSIBILITY - Ghaida alzahrani; Jamaldeen Faleel (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Islamic banks established since a long time and the first fully fledged Islamic bank establish according to the provisions of Islamic Sharia in 1975, which is a Dubai Islamic Bank. The concept of the Islamic Bank has spread dramatically, even in non-Islamic countries due to its solid foundations and based on justice, equality and prevention of monopoly and the interest. One of the main points focus in bank are Social Responsibility, where it is one of the most important concepts that urges us by our Islamic religion, however there is a shortage in clarifying the mechanism of action of Islamic banks in terms of corporate social responsibility. The point of research is to examine the genuine thought of Islamic bank and their connection with corporate social obligation in Saudi Arabia. The examination endeavors to assess the example and inclinations of CSR rehearses by Islamic banks. It likewise attempts to discover the impact of Islamic Tenets on the CSR practices of Islamic banks. To answer these inquiries, two Islamic banks in Saudi Arabia were taken as study, the investigation demonstrate that the bank are rehearsing the base CSR and the client's suppositions affirmed that Islamic banks have a job yet are few and don't diverse altogether from different banks.